Visual Representations of Bullying by Secondary School Students: A Gender-Based Approach - Moral Tabernero, Blanca Omayra (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2021)
The purpose of this study is to examine traditional bullying and cyberbullying experiences through gender consideration. Participants were youth from second and fourth year studying at a secondary school located in the city of Guadalajara (Spain). They portrayed their vision of bullying through the drawing technique. The analysis proceeded by making an objective preliminary examination and a following discussion reporting the main findings and conclusions. Results revealed that male teenagers are more likely to engage in and suffer physical aggressions, exclusion group and cyberbullying, whereas female teenagers do not comprise the common aggressor type but suffer verbal aggression, exclusion forms, cyberbullying and gender-based harassment.